Genome-wide identification reveals conserved carbohydrate-active enzyme repertoire in termites - He, Shulin; Chakraborty, Amrita; Li, Fei; Zhou, Cao; Zhang, Binchuan; Chen, Bin; Jiang, Bin (Frontiers in Forests and Global Change, 2023)
Termites play an important role as decomposers of organic matter in forests by utilizing their gut symbionts and associated carbohydrate-active enzymes (CAZymes) to digest wood materials. However, there is a limited understanding of the entire repertoire of CAZymes and their evolution in termite genomes. Here we identified the gene families of CAZymes in publicly available termite genomes and analyzed the evolution of abundant gene families. We found that 79 CAZyme gene families from the carbohydrate-binding module and four CAZyme classes, including Glycosyl Transferase (GT), Glycoside Hydrolase (GH), Auxiliary Activity (AA) and Carbohydrate Esterase (CE), were present in termites with minor variations across termite species except for a few gene families. The gene trees of the large and conserved gene families have several groups of genes from all species, and each group encodes enzymes with complete corresponding domains. Three gene families, namely GT1, GH1 and AA3, exhibited significant variations in gene numbers and experienced several losses and a few duplications, which might be related to their rich gut symbionts and newly gained functions. Furthermore, the overall expression of CAZymes appears to have a caste- and tissue-specific pattern, reflecting a division of labor in termite colonies. Overall, these results reveal a likely stable CAZyme repertoire in termites and pave the way for further research on the functional contribution of termites to wood digestion.